Anthropomorphic tissue-mimicking phantoms for oximetry validation in multispectral optical imaging - Dreher, Kris; Gröhl, Janek; Grace, Friso; Ayala, Leonardo; Nölke, Jan-Hinrich; Bender, Christoph J.; Watt, Melissa J.; White, Katie-Lou; Tao, Ran; Johnen, Wibke; Tizabi, Minu; Seitel, Alexander; et al. (Journal of biomedical optics, 2025)
SignificanceOptical imaging of blood oxygenation (sO2) can be achieved based on the differential absorption spectra of oxy- and deoxyhemoglobin. A key challenge in realizing clinical validation of the sO2 biomarkers is the absence of reliable sO2 reference standards, including test objects.AimTo enable quantitative testing of multispectral imaging methods for assessment of sO2 by introducing anthropomorphic phantoms with appropriate tissue-mimicking optical properties.ApproachWe used the stable copolymer-in-oil base material to create physical anthropomorphic structures and optimized dyes to mimic the optical absorption of blood across a wide spectral range. Using 3D-printed phantom molds generated from a magnetic resonance image of a human forearm, we molded the material into an anthropomorphic shape. Using both reflectance hyperspectral imaging (HSI) and photoacoustic tomography (PAT), we acquired images of the forearm phantoms and evaluated the performance of linear spectral unmixing (LSU).ResultsBased on 10 fabricated forearm phantoms with vessel-like structures featuring five distinct sO2 levels (between 0 and 100%), we showed that the measured absorption spectra of the material correlated well with HSI and PAT data with a Pearson correlation coefficient consistently above 0.8. Further, the application of LSU enabled a quantification of the mean absolute error in sO2 assessment with HSI and PAT.ConclusionsOur anthropomorphic tissue-mimicking phantoms hold potential to provide a robust tool for developing, standardising, and validating optical imaging of sO2.
Gesehen am 09.12.2025